ISOLATION AND IDENTIFICATION OF FUNGI ASSOCIATED WITH DIFFERENT SPECIES OF STORED GRAINES - SAIDO, KHADEEJA A.; MOHAMMED, HALBEN I.; HALEEM, RAED A. (Journal of Duhok University, 2021)
This study was conducted on different species of stored grains obtained from Duhok Province, Kurdistan Region, of Iraq to investigate the occurrence of seed borne fungi. Nine types of grains were collected and two methods were selected (agar plate method and blotter method) for fungal isolation. Atotal of 19 species assigned to 13 genera were identified. The high frequent genera were Aspergillus (4species), Penicillium, Alternaria and Fusarium (2 species), while other genera include Rhizopus,Cladosporium, Stemphylium, Ulocladium, Humicola, Bipolaris, Curvularia Phoma and Rhizoctonia were represented only in a single species. The results showed a variation in the fungal species andcontamination percentage according to the detection and incubation methods. The lowest occurrence percentage was detected in lentils seeds with only one genus represented by Penicillium spp., while the highest occurrence percentage was detected with Chickpea seeds represent by six genera. The most common fungal genera displayed by agar plate method in wheat and chickpea were Rhizoctonia sp.(34.1%) and Penicillium sp. (42.5%) respectively. The highest fungal detection by blotter method was recorded with barley seeds while the lowest was chickpea seeds. The most common fungal genera recorded by blotter method under room temperature after 7 days and 14 days was Penicillium spp, with a percent 100% from chickpea seeds followed by Aspergillus spp with percent of (66.7%, 47.6%) frombarley and raisin seeds respectively. While the highest frequent fungus in seeds incubated at 25°C after 7 and 14 days was Aspergillus parasiticus (88.9%) from mash seeds and Rhizopus sp. (80.1%) from lima bean respectively. Blotter method considered an efficient and economically reliable method.